Translation of Proper Names in Hong Kong: Media and Official Usage at the Turn of the Twentieth Century - Chan, Clara Ho-yan (Hikma, 2018)
This paper aims to describe some changes to the translation of foreign proper names in Hong Kong at the turn of the twentieth century, that is, the 10-year span a few years after the 1997 handover to China. Due to an array of historical reasons and transliteration differences, there has been great variation in the Chinese translation of proper names across the Mainland, Hong Kong and Taiwan. To determine the possible influence of the change of sovereignty on how proper names are translated and used in this post-colonial, Cantonese-speaking city, where both Chinese and English are official languages, a number of transliterated place and personal names are taken from government documents and media texts for examination. The source language of most of these names is English. Several examples are also cited to show that the Mainland media has also adopted translated proper names customarily used in Hong Kong, indicating language borrowing is taking place. An attempt is made to theoretically explain the underlying causes of this translational change using Lefevere’s “rewriting” perspectives of patronage, ideology and poetics, and general theories on language change.